Phalaenopsis LEAFY COTYLEDON1-Induced Somatic Embryonic Structures Are Morphologically Distinct From Protocorm-Like Bodies - Chen, Jhun-Chen; Tong, Chii-Gong; Lin, Hsiang-Yin; Fang, Su-Chiung (Frontiers in Plant Science, 2019)
Somatic embryogenesis is commonly used for clonal propagation of a wide variety of plant species. Induction of protocorm-like-bodies (PLBs), which are capable of developing into individual plants, is a routine tissue culture-based practice for micropropagation of orchid plants. Even though PLBs are often regarded as somatic embryos, our recent study provides molecular evidence to argue that PLBs are not derived from somatic embryogenesis. Here, we report and characterize the somatic embryonic tissues induced by Phalaenopsis aphrodite LEAFY COTYLEDON1 (PaLEC1) in Phalaenopsis equestris. We found that PaLEC1-induced somatic tissues are morphologically different from PLBs, supporting our molecular study that PLBs are not of somatic embryonic origin. The embryonic identity of PaLEC1-induced embryonic tissues was confirmed by expression of the embryonic-specific transcription factors FUSCA3 (FUS3) and ABSCISIC ACID INSENSITIVE3 (ABI3), and seed storage proteins 7S GLOBULIN and OLEOSIN. Moreover, PaLEC1-GFP protein was found to be associated with the Pa7S-1 and PaFUS3 promoters containing the CCAAT element, supporting that PaLEC1 directly regulates embryo-specific processes to activate the somatic embryonic program in P. equestris. Despite diverse embryonic structures, PaLEC1-GFP-induced embryonic structures are pluripotent and capable of generating new shoots. Our study resolves the long-term debate on the developmental identity of PLB and suggests that somatic embryogenesis may be a useful approach to clonally propagate orchid seedlings.